Image quality chest radiographs. emergency central hospital Antonio María Pineda. Barquisimeto, Venezuela (Revista Venezolana de Salud Pública, 2018)
With the purpose of assessing the quality of diagnostic image of chest radiographs from emergency department of University Central Hospital “Dr. Antonio Maria Pineda”, a transversal descriptive study was executed through a systematic revision of chest x-rays, a sample of 100 radiographs was selected, in a non-probable manner in a term of 30 days. These were compared to the quality criteria of European “Guidelines on Quality Criteria for Diagnostic Radiographic Images”, based on anatomical features seen on the image.
Keywords: chest radiographs; quality image; diagnostic criteria